REFERATUL CA INSTRUMENT AL MANAGEMENTULUI CALITĂŢII - USM ADMIN (Moldova State University, 2007)
The article treats the most controversial subjects of educational sciences nowadays - the quality management. The teacher as the manager of the entire process of teaching - learning - assessment has not only to control but to guarantee its quality as well. The teacher `s task is to make the student responsible for the quality of the learning process and to give the proper tools in this context too. This paper raises the method of using the report as an instrument of quality management.